2019
DOI: 10.1504/ijspm.2019.097717
|View full text |Cite
|
Sign up to set email alerts
|

Coloured Petri net for modelling and improving emergency department based on the simulation model

Abstract: Emergency department (ED) is one of the most complex systems, due to its unstable environment and the stochastic characteristics of patient flows, pathologies, and limited resources, which lead to a long waiting time. Effective management of patient flows for 'ED' services has become a critical matter for most hospital supervisors. Many authors have tried to solve those issues based on different methodologies, with shared aims represented in the optimisation of patient care, by minimising patient waiting time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…For example, Ajmi et al [83] developed an agent-based dynamic optimization model for improving several performance indicators (LOS, remaining patient care load, and cumulative waiting time) in EDs. OR-based studies addressing long LOS are evidenced in Chan et al [91], Derni et al [87], Liu et al [95], and Oueida et al [86,96]. Apart from the aforementioned single techniques, less popular methods like critical pathways [88,89,97], pivot nursing [92], and process redesign [94] were also used by some practitioners and researchers to diminish the total burden produced by long ED-LOS.…”
Section: Papers Focusing On Reducing the Extended Losmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ajmi et al [83] developed an agent-based dynamic optimization model for improving several performance indicators (LOS, remaining patient care load, and cumulative waiting time) in EDs. OR-based studies addressing long LOS are evidenced in Chan et al [91], Derni et al [87], Liu et al [95], and Oueida et al [86,96]. Apart from the aforementioned single techniques, less popular methods like critical pathways [88,89,97], pivot nursing [92], and process redesign [94] were also used by some practitioners and researchers to diminish the total burden produced by long ED-LOS.…”
Section: Papers Focusing On Reducing the Extended Losmentioning
confidence: 99%
“…Similar objectives were pursued by Bordoloi and Beach [151] who, unlike the previous work, used optimization models encompassing the entire patient journey within the ED. Single OR-based approaches are also extensively used in Ajmi et al [83], Derni et al [87], Leo et al [153], Meng et al [152], Nezamoddini and Khasawneh [154], and Oueida et al [96]. Other non-hybrid methods that have been employed for tackling this ED deficiency are as follows: REACT [91], pivot nursing [92], process redesign [94,156], regression [157,158], nurse navigator [160], Iowa model of evidence-based practice [161], CQI [81,155], and ED dashboard/reporting [98].…”
Section: Papers Focusing On Reducing the Waiting Timementioning
confidence: 99%
See 1 more Smart Citation
“…Papers evidencing the use of process improvement techniques for shortening LOS within EDs. Ajdari et al (2018);Best et al (2014); Bokhorst and van der Vaart (2018); Coughlan et al, (2011); Gul and Guneri (2012) Fernandes, Christenson, and Price (1996); Higgins III and Becker (2000); Lovett et al (2014); Preyde et al(2012); Rehmani and Amatullah (2008) Continuous quality improvement Ajmi et al (2019) Agent-based dynamic optimization Haydar et al (2016); Prybutok (2018) PDSA (Plan, Do, Study, Act) cycle ; Derni et al (2019) Petri nets Bellew et al (2018); Than et al (2018) Critical pathways Brouns et al (2015) Cohort study Chan et al (2005) Rapid Entry and Accelerated Care at Triage (REACT) Christensen et al (2016) Pivot nursing Christianson et al (2005) Six sigma DeFlitch et al (2015) Process redesign Liu et al (2017) Agent-based model Resource Preservation Net (RPN) Sloan et al (2009) Evidence-base care pathways Stone-Griffith et al ( 2012 Lee et al (2015) Machine learning, Simulation, Optimization Lo et al (2015) Lean principles, Simulation, Continuous process improvement Oueida et al (2019) Discrete-event simulation, Optimization Rachuba et al (2018) Process mapping, Discrete-event simulation Romano et al (2015) System dynamics simulation, Lean techniques, Causal loop diagram Ross et al (1997) Critical (2016) who merged simulation with queuing analysis for shortening the median LOS in an adult ED located in New Jersey. In this case, the results evidenced that this measure was shortened from 192 to 112 min.…”
Section: Papers Focusing On Reducing the Extended Losmentioning
confidence: 99%
“…The reported literature revealed that 12.5% (n = 9 papers) of the papers using single approaches, incorporate the application of these methods when addressing the extended LOS problem. In this respect, Kaushik et al (2018) Chan et al (2005), Derni et al (2019), Liu et al (2017),…”
Section: Authors Technique Type Singlementioning
confidence: 99%